Turn clicks into customers : proven marketing techniques for converting online traffic into revenue - Forrester, Duane (New York : McGraw-Hill, 2010)
This book reveals proven techniques not only for standing out in a crowded marketplace but also for reaching customers who are most eager to buy your products or services.--[book cover]
Includes index.
Keywords: Internet marketing; Internet advertising; Customer relations